2021
DOI: 10.3389/feduc.2021.628784
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Civic Engagement Self-Efficacy Varies Across Socioscientific Issues Contexts

Abstract: In STEM learning focused on science literacy, socioscientific issues instruction is often proposed as a way to bolster students’ civic engagement, however few studies in science education have explicitly examined this connection. We define civic engagement as the work of influencing legitimately public matters using means within the existing political structure. In this work we investigate students’ feelings of self-efficacy for this type of civic engagement in the context of four socioscientific issues (prair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Self-efficacy was first introduced by Bandura (1977, 1978), its applications have been extended to various academic disciplines. Previous studies found if individuals do not feel that their actions will be effective within the system they are engaging, they will avoid or reduce their involvement (Beaumont, 2010; Cicognani, 2014); It is also found that strong sense of self-efficacy positively predicts adolescents’ intentions to participate in civic activities (Ainley & Schulz, 2011; Manganelli et al, 2014; Schulz et al, 2010) as well as college students’ actual participation in civic activities (Dauer et al, 2021; Krampen, 2000; Pasek et al, 2008). Moreover, Pastorelli et al (2001) argued successful civic engagement requires motivation and continued actions on the part of the individual.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Self-efficacy was first introduced by Bandura (1977, 1978), its applications have been extended to various academic disciplines. Previous studies found if individuals do not feel that their actions will be effective within the system they are engaging, they will avoid or reduce their involvement (Beaumont, 2010; Cicognani, 2014); It is also found that strong sense of self-efficacy positively predicts adolescents’ intentions to participate in civic activities (Ainley & Schulz, 2011; Manganelli et al, 2014; Schulz et al, 2010) as well as college students’ actual participation in civic activities (Dauer et al, 2021; Krampen, 2000; Pasek et al, 2008). Moreover, Pastorelli et al (2001) argued successful civic engagement requires motivation and continued actions on the part of the individual.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In previous work, instruction using SDM has shown gains in many areas within STEM literacy, including socioscientific reasoning competencies (i.e., complexity, perspectivetaking, inquiry, and skepticism) [12], learner self-efficacy in finding and applying scientific evidence [24], use of explicit scientific evidence to support claims [37], awareness of multiple potential solutions to SSI [37], civic engagement attitudes [57], and social justice, interpersonal and problem-solving, and political awareness skills [57].…”
Section: Decision-making and Critical Integrative Argumentationmentioning
confidence: 99%
“…Many examples of teaching with a scientific civic engagement approach are in practice today. For example, STEM educators have been incorporating different modes of activities in their courses, such as encouraging students to engage in decision making around socioscientific issues ( Dauer et al. , 2021 ), using citizen science to learn about diversity and its impact on the ecosystems ( Vance-Chalcraft et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 2021 ) and/or emphasizing environmental education that helps strengthen school–community relationships by working on issues related to sustainability and climate change ( Flowers and Chodkiewicz, 2009 ). Experiences such as these help students develop their ability to use scientific rationale when making complex decisions about practices that affect their communities ( Dauer et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 99%